-(-n+2)-2n=

Simple and best practice solution for -(-n+2)-2n= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(-n+2)-2n= equation:


Simplifying
-1(-1n + 2) + -2n = 0

Reorder the terms:
-1(2 + -1n) + -2n = 0
(2 * -1 + -1n * -1) + -2n = 0
(-2 + 1n) + -2n = 0

Combine like terms: 1n + -2n = -1n
-2 + -1n = 0

Solving
-2 + -1n = 0

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + -1n = 0 + 2

Combine like terms: -2 + 2 = 0
0 + -1n = 0 + 2
-1n = 0 + 2

Combine like terms: 0 + 2 = 2
-1n = 2

Divide each side by '-1'.
n = -2

Simplifying
n = -2

See similar equations:

| z+12=-7 | | -11x-4=-191 | | 3(x+2)-6=4x | | .4x+1.18=3.1(2-0.01x) | | 5x+15+53=143 | | 8(4u-u)+u=8+u | | (2p-3)=7 | | -c=-2c-9 | | 5x+15+143= | | 2x-8x=0 | | -4d=-6d-10 | | 4a^2+20ad+25d^2= | | -2+5(4+3r)= | | 10x+5y=12 | | x+54*8x= | | 45x^2-20y^2=0 | | 12-2y=10y-10 | | y-2+5y=16 | | [x+3]+6=-4 | | 9m-6m+4=16 | | -14(-9+n)=98 | | [x+3]+6=4 | | (75*h)+50=(55*h)+120 | | 6x+120= | | 3y+3=9-9y+18 | | -(5x+12)=18 | | 7(4.3+x)= | | 2x+3=12x+8 | | 1/4(8d-4)=d+8-2d | | 3(x)-5(13)= | | 4(7x+7)=28x+28 | | 17(n+18)=612 |

Equations solver categories